Characterizing conversion points and complex infrastructure systems: Creating a system representation for agent‐based modeling. Issue 6 (22nd April 2014) - Varga, Liz; Grubic, Tonci; Greening, Philip; Varga, Stephen; Camci, Fatih; Dolan, Tom; Gilbert, Nigel; Bullock, Seth
<x xml:space="preserve">Abstract</x> Infrastructure, which is used to extract, transport, store, and transform resources into products or services to meet our utility needs faces numerous challenges caused by the agency of the various actors in the system. To understand these challenges, we propose it is necessary to move beyond considering each utility system as a distinct silo. In this paper, a conversion points approach is developed to characterize multiutility systems at any scale and for any specific or theoretical location. The story is told of the development of a conversion points approach and its application is examined using an agent‐based model. Transport, energy, water, waste, and telecommunications systems are governed and run independently but in practice are highly interdependent. A way to represent all utility systems in an integrated way is described and the benefits of this representation are applied to UK household consumers. © 2014 Wiley Periodicals, Inc. Complexity 19: 30–43, 2014